The effect of the Dubai Metro on the value of residential and commercial properties - Sara Ishaq Mohammad; Daniel J. Graham; Patricia C. Melo (Journal of Transport and Land Use)
This paper analyzes the impact of the newly operated Dubai Metro on the sale transaction value of dwellings and commercial properties. The effect is estimated for properties within different catchment zones of a metro station using difference-in-differences and hedonic pricing methods on both repeated cross-sectional data and pseudo panel data. Our estimates show a positive effect of the metro on sale values of both residential and commercial properties, although the effect is stronger for commercial properties. The models also reveal that the effect of the metro on the value of dwellings and commercial properties is largest within 701 to 900 meters of a metro station and is about 13 percent and 76 percent, respectively.